PENERAPAN PROJECT BASED LEARNING (PjBL) DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI PELESTARIAN DAN PERUBAHAN LINGKUNGAN KELAS X.2 SMA NEGERI 2 PALEMBANG - Tiara Ulandari; Zuriah Susilawati; Riyanto Riyanto (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
In general, students often feel bored with the learning process so that the subject matter is easily forgotten, this can affect the learning outcomes of a student. The purpose of this research activity is to determine the effectiveness of the project-based learning model in improving the learning outcomes of class X.2 students of SMA N 2 Palembang City on the topic of Environmental Conservation and Change. The method used was Classroom Action Research (PTK) with a research population of SMA N 2 students and the research sample was class X.2 students of 42 students. The results of individual learning mastery on environmental preservation and change material are seen as indicators of success. In cycle I obtained individual learning mastery of 45.23% with the number of students with scores > 70 of 19 students and students with grades < 70 of 23 students. In cycle II it increased by 80.95%, with the value of the number of students who scored > 70 as many as 34 students and students with grades < 70 as many as 8 students. The research results prove that student learning outcomes can be increased effectively by applying the Project Based Learning learning model.